2009
DOI: 10.2337/dc09-0273
|View full text |Cite
|
Sign up to set email alerts
|

TSH-Lowering Effect of Metformin in Type 2 Diabetic Patients

Abstract: OBJECTIVETo assess the interplay between metformin treatment and thyroid function in type 2 diabetic patients.RESEARCH DESIGN AND METHODSThe acute and long-term effects of metformin on thyroid axis hormones were assessed in diabetic patients with primary hypothyroidism who were either untreated or treated with levothyroxine (L-T4), as well as in diabetic patients with normal thyroid function.RESULTSNo acute changes were found in 11 patients with treated hypothyroidism. After 1 year of metformin administration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
129
4
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(162 citation statements)
references
References 9 publications
20
129
4
5
Order By: Relevance
“…The results of the present retrospective study indicate that the TSH-lowering effect of metformin, previously observed in hypothyroid subjects (13), also occurs in euthyroid diabetic patients with basal TSH in the uppernormal range. This effect of metformin appears to occur independently of the presence of AbTPO.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The results of the present retrospective study indicate that the TSH-lowering effect of metformin, previously observed in hypothyroid subjects (13), also occurs in euthyroid diabetic patients with basal TSH in the uppernormal range. This effect of metformin appears to occur independently of the presence of AbTPO.…”
Section: Discussionsupporting
confidence: 52%
“…We also reported a significant reduction of serum TSH levels in diabetic patients with primary untreated hypothyroidism (13). More recently, a decrease in serum TSH was also observed in hypothyroid women being treated with metformin for a coexistent polycystic ovarian syndrome (14,15).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…While three studies in patients with hypothyroidism and/or levothyroxine treatment showed a reduction of serum TSH levels under metformin treatment (9,10,11), a retrospective study demonstrated significantly higher serum TSH levels in euthyroid patients with T2DM treated with metformin compared with those treated with other diabetic agents (12). However, in that study, metformin use was not associated with serum TSH levels after adjustment for several potential confounding factors of which goiter was the only significant one (12).…”
Section: Introductioncontrasting
confidence: 43%
“…Many other literatures have also documented an association of thyroid abnormalities, notably overt and subclinical hypothyroidism as well as autoimmune thyroiditis with GDM [56][57][58][59][60] . This correlation has been substantiated by depiction of an inverse association between Metforfin and TSH level 61,62,63 . Hence, screening for thyroid dysfunction in diabetes patients, ät-risk" patients for GDM, with anti-TPO antibody positivity, or with TSH concentrations in the upper limits of normal range has been advised by many studies.…”
Section: Discussionmentioning
confidence: 90%